Modeling Choropleth Maps of the Urban Heat Island in Erbil City Using Remote Sensing - Saad Thamer Ibrahim; dr.Hamda Hamudi Sheet; dr.Faiq Hassan Muhammed (Journal of College of Education, 2025)
Abstract: The aim of this study is to use the effective choropleth mapping method with the visual variable of color to represent thermal island data in Erbil city for the period of 1990 to 2023. Thermal island data were extracted using the Google Earth Engine platform, which provides land surface temperature (LST) data. Through this platform, LST data are subjected to a set of international standards to identify the prevailing thermal island pattern in the study area. The thermal island data were represented in several cartographic models as follows: (Model 1 used red, orange, and yellow), (Model 2 used red and its gradients), (Model 3 used red, yellow, and blue), and (Model 4 used black, gray, and blue). The results indicated that Model 1 was the most suitable for representing thermal island data in the study area, as the colors used in this model best simulate the phenomenon and the real-world conditions. The representation of these models relied on the Geographic Information System (GIS) software environment, specifically ArcGIS Pro.